Firefighters exposure to fire emissions: Impact on levels of biomarkers of exposure to polycyclic aromatic hydrocarbons and genotoxic/oxidative-effects - Oliveira, M (2020)
Firefighters represent one of the riskiest occupations, yet due to the logistic reasons, the respective exposure assessment is one of the most challenging. Thus, this work assessed the impact of firefighting activities on levels of urinary monohydroxyl-polycyclic aromatic hydrocarbons (OHPAHs; 1-hydroxynaphthalene, 1-hydroxyacenaphthene, 2-hydroxyfluorene, 1-hydroxyphenanthrene, 1-hydroxypyrene, 3-hydroxybenzo(a)pyrene) and genotoxic/oxidative-effect biomarkers (basal DNA and oxidative DNA damage) of firefighters from eight firehouses. Cardiac frequency, blood pressure and arterial oxygen saturation were also monitored. OHPAHs were determined by liquid-chromatography with fluorescence detection, while genotoxic/oxidative-effect biomarkers were assessed by the comet assay. Concentrations of total OHPAHs were up to 340% higher (p ≤ 0.05) in (non-smoking and smoking) exposed workers than in control subjects (non-smoking and non-exposed to combat activities); the highest increments were observed for 1-hydroxynaphthalene and 1-hydroxyacenaphthene (82–88% of ∑OHPAHs), and for 2-hydroxyfluorene (5–15%). Levels of biomarker for oxidative stress were increased in non-smoking exposed workers than in control group (316%; p ≤ 0.001); inconclusive results were found for DNA damage. Positive correlations were found between the cardiac frequency, ∑OHPAHs and the oxidative DNA damage of non-smoking (non-exposed and exposed) firefighters. Evidences were raised regarding the simultaneous use of these biomarkers for the surveillance of firefighters’ health and to better estimate the potential short-term health risks.